PREVENTING VIOLENCE AGAINST CHILDREN IN THE FAMILY: A MODERN PEDAGOGICAL PROBLEM - Fedorchenko, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article is devoted to the urgent problem of preventing violence (bullying) in the family. The purpose and objectives of the article are to analyze the issue of preventing violence against children within families, to identify and characterize typologies of families where violence occurs, and to present data from a pedagogical experiment on the phenomenon under study. To address this issue and explore possible solutions, a range of methods was employed: analysis, synthesis, comparison, and generalization of theoretical sources in psychology, pedagogy, law, and sociology; review of documents related to the legal and regulatory framework; surveys, questionnaires, interviews, and discussions. In the process of theoretical understanding of the problem, the essence of the concept of “violence against children in the family” as a phenomenon was analyzed – physical, psychological, sexual violence or lack of education and care for children by parents; child abuse can include any act of violence, neglect, abuse, or failure, unwillingness, or inability to nurture that results in actual or potential harm to a child. The results of a survey of teenagers regarding their relationship with their parents, including the cruel treatment of parents to children, are presented. The characteristics of the typology of families where violence is committed against teenagers are determined: families with a low level of parents’ psychological and pedagogical culture, their social skills, families with conflictual family relationships, problematic parent-child relationships, powerful and authoritarian families, families where parental skills and feelings are underdeveloped, parents’ negative attitude towards others and inadequate social expectations towards the child, emotional and physical isolation of the family, maternal derivation. The conclusions underscore the pivotal role of the audience in working with families where parents use violent methods of upbringing towards teenagers. It is crucial to shift the emphasis to solving the following issues: constant monitoring of families where children are abused; raising parents’ awareness of violence and its consequences for children; awareness of parents’ responsibility for raising children in the family; raising the level of legal culture, knowledge of legislative norms; improving the ability of effective communication between parents and teenagers; definition of goals, which will be provided by the strategy of organizing an effective partnership with the family of a specific educational institution; forming a non-violent model of behaviour and resolving conflicts peacefully; involvement of social pedagogues, psychologists, social services, juvenile prevention workers in working with parents to prevent and overcome violence against teenagers. The article’s practical significance is that its materials can be used to organize educational work in institutions of general secondary education and out-of-school education. They can potentially inspire positive change in the field of child welfare, offering hope to scientists, graduate students, and students.